Pengaruh Stress Kerja, Budaya Organisasi, dan Kompensasi terhadap Kinerja Tenaga Terdidik Universitas Muhammadiyah Surakarta - Muhammad Alwi Shihab; Kusdiyanto (Jurnal Manajemen Dirgantara, 2024)
The aim of this study was to analyze the effect of work stress, organizational culture, and compensation on the performance of educated personnel of Surakarta Muhammadiyah University. This research uses quantitative methods. The population in this study were all educated personnel of Universitas Muhammadiyah Surakarta. The sampling method of this research is non-probability sampling with purposive sampling technique. The data sources of this research are primary data and secondary data. The data collection technique used a questionnaire. The research data analysis technique with the help of SPSS software. The results of this study are that Job Stress has a significant effect on Employee Performance. Organizational Culture has a significant effect on Employee Performance. Compensation has a positive effect on Employee Performance.